State Sovereignity in Airspace - Abdurrasyid, Priyatna (UI Scholars Hub, 2009)
This article concentrates on the overall development of the historical air sovereignty concept since the time of Socrates/Plato, Ptolemius, Copernicus, Galilei-Galileo, Einstein and Stephen Hawkings. In 1994, finally, this air sovereignty concept was strongly embedded in Article 1 of the Chicago Convention 1944, after being analyzed/regulated at the Diplomatic Conference and the Paris Convention 1919.